EP346 The prognostic value of hematologic parameters in cervical cancer patients receiving radiation therapy. (1st November 2019) - Kim, YJ; Kim, YS; Lee, KB; Shin, JW; Lee, SH
Abstract : Introduction/Background: The aim of this study was to determine the prognostic roles of hematologic parameters in patients with cervical cancer received definitive radiation therapy (RT). Methodology: A total of 128 patients received definitive RT for cervical cancer were enrolled in this study.The clinical data and hematologic parameters were retrospectively reviewed, and analyzed their prognostic roles for survival.Theneutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and lymphocyte-to-monocyte ratio (LMR)) and the changes between pre- and post-treatment in hematologic parameters (ΔNLR, ΔPLR, and ΔLMR) were alsocalculated to analyze the specific roles for survival. Results: The median follow-up was 36.9 months, with a range of 1–114 months.The 5-year overall survival rate and progression free survival rate was 65.8% and 46.4%, respectively. High pretreatment NLR (NLR>2.84) was a poor prognostic factor for progression-free survival (PFS; HR=2.789; 95% CI 1.497–5.197) and overall survival (OS; HR=4.191, 95% CI 2.002–8.773). ΔNLR>0 was significantly associated with lower progression-free survival(HR=2.942, 95% CI 1.458–5.938) and overall survival (HR=3.802, 95% CI 1.487–9.725). In addition to NLR and ΔNLR, age (age≤55; PFS: HR=2.538; 95% CI 1.491–4.320; OS: HR=3.475; 95% CI 1.652–7.310) and FIGO stage (III–IV; PFS: HR=3.067; 95% CI 1.790–5.253; OS: HR=4.252; 95% CI 1.974–9.157) were identified as poor predictors of PFS and OS, whereas white blood cell (WBC<5710; PFS: HR=1.961; 95% CI 1.044–3.682) was significantly predictive of PFS only. Conclusion: Both pretreatment NLR and ΔNLR were independent prognostic factors for cervical cancer patients treated with RT. Risk scoring system-based prognostic factor analysis could be used to help develop optimized treatment plans for cervical cancer patients receiving RT. Disclosure: Nothing to disclose.